2013
DOI: 10.1093/cvr/cvt231
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow deficiency of TRPC3 channel reduces early lesion burden and necrotic core of advanced plaques in a mouse model of atherosclerosis

Abstract: Bone marrow deficiency of TRPC3 has a dual beneficial effect on lesion progression by reducing cellularity at early stages and necrosis in the advanced plaques. Our findings represent the first evidence for a role of a member of the TRPC family of cation channels in mechanisms associated with atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 27 publications
3
75
3
Order By: Relevance
“…Lungs have a high content of endothelial cells, facilitating immunoblot detection of HA-tagged TRPC3 of endothelial origin. Contrarily to what is observed with other endothelial promoters (e.g., Tie2, Ve-cadherin), there was no expression of TRPC3-HA in bone marrow-derived macrophages from TgEST3ApoEKO mice, which is of importance as we recently showed that macrophage TRPC3 influences the characteristics of early and advanced atherosclerotic lesions of ApoeKO mice by virtue of its role in mechanisms associated to macrophage apoptosis (11,15). Immunohistochemistry for HA epitope in aortic root sections from the transgenic mice confirmed endothelial localization of TRPC3-HA (Fig.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Lungs have a high content of endothelial cells, facilitating immunoblot detection of HA-tagged TRPC3 of endothelial origin. Contrarily to what is observed with other endothelial promoters (e.g., Tie2, Ve-cadherin), there was no expression of TRPC3-HA in bone marrow-derived macrophages from TgEST3ApoEKO mice, which is of importance as we recently showed that macrophage TRPC3 influences the characteristics of early and advanced atherosclerotic lesions of ApoeKO mice by virtue of its role in mechanisms associated to macrophage apoptosis (11,15). Immunohistochemistry for HA epitope in aortic root sections from the transgenic mice confirmed endothelial localization of TRPC3-HA (Fig.…”
Section: Resultssupporting
confidence: 48%
“…Endothelial inflammatory signaling, monocyte recruitment, and the balance between survival and apoptosis of lesional macrophages, are all fundamental in initiation and progression of atherosclerotic lesions as well as in determining the fate of the plaque at advanced stages (9,10). A paramount piece of experimental evidence supporting a role of TRPC3 in atherogenesis was provided by our recent findings in a mouse model of atherosclerosis demonstrating that TRPC3 contributes to mechanisms underlying necrotic core growth in advanced atherosclerotic plaques of Apoe knockout (ApoeKO) mice by influencing the rate of apoptosis of lesional macrophages (11). However, the expression of TRPC3 is ubiquitous and macrophages are not the sole atherorelevant cells where this channel is present.…”
mentioning
confidence: 99%
“…In ApoE-deficient mice transplanted with the bone marrow of TRPC3-null animals and kept on a high-fat diet, atherosclerotic plaques occurred later and were smaller with a reduced necrotic core compared with control subjects (Tano et al, 2014).…”
Section: Transient Receptor Potential Channels In Cardiovascular Dmentioning
confidence: 94%
“…There is preliminary evidence to implicate TRPC3 in efferocytosis ("burying the dead cells"). Bone marrow-derived macrophages obtained from TRPC3(2/2) mice showed decreased survival and impaired efferocytosis (Tano et al, 2011(Tano et al, , 2014. If so, TRPC3 may play an important role not only in disease initiation (endothelial damage) but also in disease progression (see Tano et al, 2012).…”
Section: Transient Receptor Potential Channels In Cardiovascular Dmentioning
confidence: 99%
“…Solanki et al [81] shown that the number of ERS-related apoptotic macrophages was increased by a deficiency of calcium-permeable channel transient receptor potential canonical 3 (TRPC3). TRPC3 reduced scavenging of apoptotic SMCs and macrophages and then allowed cells to undergo secondary necrosis, thereby increasing the thrombogenicity of the plaque [82] . Suppression of ERS decreased the number of apoptotic macrophages [83] .…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%